Alessandro Magno, Eracle e la leonté nella glittica ellenistica e romana - Giovanni Frumusa (Lanx, 2009)
The study of a nephrite jade, dated from the end of first century b.C. to first century a.D., found in 1976 in Forum’s Baths in Martigny and portraying Alexander the Great’s profile with leonté, has been the starting point for examining the iconographical evolution of this type in Hellenistic and Roman glyptics. The examinated pieces, covering a period of time from third century b.C. to first century a.D., document the existence of several models: in the first one the relation between leonté and human head is well-proportioned, mane is not thick, mandible places under the ear; in the second one mane is bulky and shoulder is in evidence; in the third one leonté moves to the back of the neck and covers temple and ear. The origin of the type is to trace back to identification between Alexander the Great and young Heracles wearing skin of Nemean lion, this connection is revealed by coinage and sculptures of Macedonian king. This iconography spread with success among Hellenistic kings and Romans.